PENGARUH PERSON-JOB FIT DAN PERSON-ORGANIZATION FIT TERHADAP KOMITMEN ORGANISASIONAL DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) - Bangun, Ollani Vabiola; Supartha, Wayan Gede; Subudi, Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.05.TAHUN 2017, 2017)
This study aimed to analyze the effect of person-job fit on OCB and organizational commitment, the effect of person-organization fit on OCB and organizational commitment. As weel as the effect of organizational commitment on organizational citizenship behavior (OCB). This research was conducted in PT. Trisaka Reksa Waluyo. Samples are taken by 73 employees with saturated sampling method. Data were collected by distributing questionnaires and using path analysis as data analysis techniques. These result indicate that person-job fit have positive and significant  effect on organizational commitmet and OCB, person-organization fit have positive and significant effect on organizational commitment but not significant to OCB. Furthermore, organizational commitment shown have positive and significant  effect on OCB. The practical implication of this research is to help organizations to recruit and have a good evaluations standart to have qualified human resource.
Keywords: Person-job fit; Person-organization fit; Organizational commitment; Organizational citizenship behavior (OCB)